A Multisite Survey of NICU Healthcare Professionals' Perceptions About Family-Centered Care. (June 2021) - Franck, Linda S.; Cormier, Diana M.; Hutchison, Jennifer; Moore, Dishon; Bisgaard, Robin; Gay, Caryl; Ngo, Samantha; Kriz, Rebecca M.; Lin, Carol; Ekno, Mary; Ribero, Denise; Sun, Yao
Abstract : Background: Family-centered care contributes to improved outcomes for preterm and ill infants. Little is known about the perceptions of neonatal intensive care unit (NICU) healthcare professionals regarding the degree to which their NICU practices or values family-centered care. Purpose: The aims of this study were to describe attitudes and beliefs of NICU healthcare professionals about family-centered care and to explore professional characteristics that might influence those views. Methods: Data were derived from the baseline phase of a multicenter quasi-experimental study comparing usual family-centered NICU care with mobile-enhanced family-integrated care. Neonatal intensive care unit healthcare professionals completed the Family-Centered Care Questionnaire—Revised (FCCQ-R), a 45-item measure of 9 core dimensions of Current Practice and Necessary Practice for family-centered care. Results: A total of 382 (43%) NICU healthcare professionals from 6 NICUs completed 1 or more of the FCCQ-R subscales, 83% were registered nurses. Total and subscale scores on the Necessary Practice scale were consistently higher than those on the Current Practice scale for all dimensions of family-centered care (mean: 4.40 [0.46] vs 3.61 [0.53], P < .001). Only years of hospital experience and NICU site were significantly associated with Current Practice and Necessary Practice total scores. Implications for Practice: Ongoing assessment of the perceptions of NICU healthcare professionals regarding their current practice and beliefs about what is necessary for the delivery of high-quality family-centered care can inform NICU education, quality improvement, and maintenance of family-centered care during the COVID-19 pandemic. Implications for Research: Further research is needed to identify additional factors that predict family-centered care perceptions and behaviors. Abstract : Supplemental Digital Content is Available in the Text.